2019
DOI: 10.1001/jamanetworkopen.2019.12409
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Frailty Scores With Hospital Readmission for Falls After Index Admission for Trauma-Related Injury

Abstract: IMPORTANCE Falls have been associated with morbidity and mortality in elderly patients. Assessment of frailty at hospital admission may help health care professionals evaluate fall risk in patients with trauma-related injury. OBJECTIVE To determine whether frailty assessed using the Canadian Study of Health and Aging Clinical Frailty Scale is associated with readmission for falls after index admission for trauma-related injury in patients aged 50 years and older. DESIGN, SETTING, AND PARTICIPANTS This retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 23 publications
4
43
0
Order By: Relevance
“…6 In a large national database of acute hospital admissions (not only trauma admissions), falls were among the leading diagnoses for 30-day posthospital readmission, particularly among older patients with a history of cognitive impairment or acute mental status change and among those for whom the index admission involved treatment for a fall injury. 6 This is similar to the outcome reported by Hatcher et al, 5 although our study 6 had a shorter follow-up period. We now know that, for patients admitted for a fall-related injury, the leading cause-of all diagnoses-for any type of 30-day readmission is a second, distinct fall.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…6 In a large national database of acute hospital admissions (not only trauma admissions), falls were among the leading diagnoses for 30-day posthospital readmission, particularly among older patients with a history of cognitive impairment or acute mental status change and among those for whom the index admission involved treatment for a fall injury. 6 This is similar to the outcome reported by Hatcher et al, 5 although our study 6 had a shorter follow-up period. We now know that, for patients admitted for a fall-related injury, the leading cause-of all diagnoses-for any type of 30-day readmission is a second, distinct fall.…”
supporting
confidence: 90%
“…4 Simpler can be better: while we know that a time-consuming comprehensive battery of functional status questions can do the job, both sets of ACS guidelines promote the use of a set of just 5 questions about activities of daily living for older patients with trauma and undergoing surgery. 2,3 The article by Hatcher et al 5 adds to the literature on trauma surgery by introducing a new clinical outcome to the many already associated with prehospital functional status: readmission for a fall injury. The authors found that frailty was associated with readmission for a fall injury within the first year and the number of falls over the first year.…”
mentioning
confidence: 99%
See 3 more Smart Citations